Systemic Inflammation and Cognitive Decrements in Patients With Stage B Heart Failure. Issue 2 (14th February 2022) - Redwine, Laura S.; Hong, Suzi; Kohn, Jordan; Martinez, Claudia; Hurwitz, Barry E.; Pung, Meredith A.; Wilson, Kathleen; Pruitt, Christopher; Greenberg, Barry H.; Mills, Paul J.
ABSTRACT: Objective: This study aimed to investigate the role of systemic inflammation in reduced cognitive functioning in patients with early-stage heart failure (HF) while determining associations with other cardiovascular risk factors. Methods: Patients with stage B HF ( n = 270; mean [standard deviation] age = 66.1 [10.1] years) were examined cross-sectionally for relationships among cardiovascular disease (CVD) and psychological risk factors, C-reactive protein (CRP), and Montreal Cognitive Assessment (MoCA) scores. A subsample ( n = 83) at high risk for stage C HF (B-type natriuretic peptide levels ≥65 pg/ml) were followed up for 12 months for relationships between CRP levels and cognitive function. Results: Baseline smoking ( χ 2 = 6.33), unmarried ( χ 2 = 12.0), hypertension ( χ 2 = 5.72), greater body mass index ( d = 0.45), and physical fatigue ( d = 0.25) were related to higher CRP levels ( p values < .05). Cross-sectionally, CRP levels were negatively related to MoCA scores, beyond CVD (Δ R 2 = 0.022, β = −0.170, p < .010) and psychological risk factors (Δ R 2 = 0.016, β = 0.145, p < .027), and related to mild cognitive impairment criteria (odds ratio = 1.35, 95% confidence interval [CI] = 1.00–1.81, p = .046). Across 12 months, B-type natriuretic peptide high-risk patients with CRP levels ≥3 mg/L had lower MoCA scores (23.6; 95% CI = 22.4–24.8) than did patients with CRP levels <3 mg/L (25.4; 95% CI = 24.4–26.5; p = .024). Conclusions: Patients with stage B HF and heightened CRP levels had greater cognitive impairment at baseline and follow-up, independent of CVD and potentially psychological risk factors. Low-grade systemic inflammation may be one mechanism involved in cognitive dysfunction at early stages of HF.